ABAP CDS Views Performance Analysis in SAP HANA - Marek GAŁĄZKA; Jerzy SZYMAŃSKI (Communications of International Proceedings, 2021)
Increasing   amount   of   data   and   the   diversity   of available data structures enable applications that can make timely decisions based on live data that, in most cases, can be evaluated without traditional application layer processing. SAP introduced the  Core  Data  Service  (CDS)  framework  as  a  data  modeling approach  in  which  Virtual  Data  Models  (VDM)  are  defined  at the  database  layer.  CDS  improve  applications  performance  by pushing  data  processing  from  the  application  to  the  database layer to reduce data movements. In this paper, we present some technical  insights  into CDS Views, including some practical rules for better performance of CDS Views.
Keywords: CDS Views; ERP systems; SAP S/4HANA; Query-optimization; Query-processing; Structured Query Language (SQL); Relational Database Management system (RDBMS).